PASRAMAN SEBAGAI MEDIA PEMBENTUK IDENTITAS PASCA KONFLIK (Studi terhadap Internalisasi Tri Hita Karana pada Masyarakat Balinuraga Lampung Selatan) - Wahyu Setiawan (Harmoni, 2015)
The use of ethnic identity as “our mode” is one of the potential factors of conflict in Lampung, especially in Balinuraga, South Lampung in October 2012. This paper attempts to examine the identity formation strategies of Balinuraga community in order to be a friendly, opend-minded, Balinese Hindu. The main media used for such formation is pasraman established in post-conflict period. The identity formation in pasraman is undertaken through internalization of religious and cultural values in the context of the Hindu concept of Tri Hita Karana. This study shows that pasraman functions as a social institution in the formation of religious identity based on the Tri Hita Karana concept through harmonizing the relationship among God, humans, and nature. The strategy is carried out through seloka, kirtanam, and reading of the scriptures, ritual stuff, intensive sekagong. These strategies can bridge the gap of religious life that originally emphasizes merely on ritual aspects and balance such ritual to the moral or ethical Hindu teachings.